2016
DOI: 10.1016/j.clinph.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Early- and late-latency gamma auditory steady-state response in schizophrenia during closed eyes: Does hallucination status matter?

Abstract: Evaluation of auditory entrainment in both open eyes and closed eyes conditions is informative. Frequency and timing information of both early-latency and late-latency responses helps to uncover different aspects of impairment in schizophrenia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Subsequently, these authors found that the time to peak "late-latency" γ-band amplitude (early-gamma = 0-100 ms, late-gamma = 200-300 ms), irrespective of phase-locking, distinguished AH from non-AH patients (ie, AH longer), and that longer time to peak was positively correlated with AH severity. 64 Using a similar paradigm, Hirano and colleagues 65 also found that phase-locking was significantly reduced in SCZ compared to controls at 40 Hz only, however, nonphase-locked mean γ-band power (amplitude) was not different between the groups at rest and was increased during 40 Hz ASSR stimulation in SCZ. Also in SCZ, AH symptoms were positively correlated with induced 40 Hz γ-band power in the left hemisphere and negatively correlated with the ASSR stimulation phaselocking factor.…”
Section: Phase Synchronizationmentioning
confidence: 94%
“…Subsequently, these authors found that the time to peak "late-latency" γ-band amplitude (early-gamma = 0-100 ms, late-gamma = 200-300 ms), irrespective of phase-locking, distinguished AH from non-AH patients (ie, AH longer), and that longer time to peak was positively correlated with AH severity. 64 Using a similar paradigm, Hirano and colleagues 65 also found that phase-locking was significantly reduced in SCZ compared to controls at 40 Hz only, however, nonphase-locked mean γ-band power (amplitude) was not different between the groups at rest and was increased during 40 Hz ASSR stimulation in SCZ. Also in SCZ, AH symptoms were positively correlated with induced 40 Hz γ-band power in the left hemisphere and negatively correlated with the ASSR stimulation phaselocking factor.…”
Section: Phase Synchronizationmentioning
confidence: 94%
“…Using simultaneous EEG-fMRI, class D microstates have been suggested to be related to a right-lateralized frontoparietal network associated with attention reorientation (Britz et al, 2010). Koenig et al used measure of phase synchrony and demonstrated a left-lateralized phase synchrony −decrease in patients with AVH during 40 Hz auditory stimulation, in contrast to a phase synchrony −increase in healthy subjects or patients without AVH (Koenig et al, 2012, Griskova-Bulanova et al, 2016). …”
Section: Eeg-based Connectivity Analysesmentioning
confidence: 99%
“…Phase-locking index (PLI, corresponding to the phase consistency over epochs) and event-related spectral perturbation (ERSP, corresponding to the average power over epochs) measures (more details can be found in Mørup et al 2007) were calculated within 38-42 Hz and -100 -0 and 200-500 ms windows, the former resulting in a baseline measure and the latter corresponding to the latelatency gamma (Tada et al 2016). Response window from 200 ms was chosen in order to exclude the impact of onset and capture both the maximum response and the steady-state part, as previously done in (Rojas et al 2011;Griskova-Bulanova et al 2016). The wavelet-transform derived measures of the late-latency gamma response were normalized by subtracting the mean of the baseline.…”
Section: Eeg Analysismentioning
confidence: 99%